Prescription of Trace Elements in Adults on Home Parenteral Nutrition: Current Practice Based on the Canadian Home Parenteral Nutrition Registry. Issue 3 (12th October 2012) - Abdalian, R.; Fernandes, G.; Duerksen, D.; Jeejeebhoy, K. N.; Whittaker, S.; Gramlich, L.; Allard, J. P.
Abstract : Background : Since the introduction of long‐term parenteral nutrition (PN), morbidity due to inadequate replacement or toxicity of routinely administered trace elements has been well described. After decades of experience, much debate still exists about optimal supplementation. In practice, trace elements (TEs) seem to be frequently provided by prescribing an all‐inclusive commercial multi‐TE admixture with little dosage flexibility. Aim : Our goal was to review TE supplementation practice among 5 PN support centers across Canada, through a retrospective review of the Canadian Home PN Registry. Methods : Baseline demographic, clinical, and biochemical parameters along with information regarding the PN prescription of 135 patients with complete records were retrieved from the registry database collected between 2005 and 2007. TE supplementation prescriptions were compared with recent guidelines as well as between groups of patients with different PN indications and dietary intake status. Consent was signed by all participating patients. Results : The average daily PN concentrations of TE were as follows: zinc, 8.6 ± 5.5 mg (130.92 ± 84.23 µmol); manganese, 452 ± 184 µg (8.22 ± 3.34 µmol); selenium, 78 ± 45 µg (0.99 ± 0.57 µmol); chromium, 11 ± 5 µg (0.21 ± 0.10 µmol); copper, 0.64 ± 0.35 mg (10.11 ± 5.58 µmol); and iodine, 77 ± 42 µg (0.61 ± 0.33 µmol). The mean daily supplementation of zinc, manganese, copper, and selenium exceeded published recommendations. Patients' underlying anatomy or indication for PN did not significantly influence decisions regarding replacement standards. Conclusion : Parenteral TE supplementation in Canadian PN programs needs to be reviewed and adjusted according to most current guidelines. This may require a reevaluation of the commercial TE preparations currently available in Canada and potential new products worldwide to avoid oversupplementation and potential toxicity.